Pengaruh Penambahan Serat Kawat Bendrat pada Beton Mutu Tinggi terhadap Kapasitas Kuat Tekan dan Kuat Lentur - Bagus, Krisna; Purwanto, Eddy; Bayzoni, Bayzoni (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
Concrete is one of the construction materials that has the advantage of being able to withstand a high compressive strength but has a low tensile strength.To overcome the weaknesses that exist in the concrete, one of the efforts applied is to add fiber in the form of bendrat wire in the concrete in order to increase the tensile strength and flexural strength of concrete. The specimens of this research are concrete cylinder with diameter 15 cm and height 30 cm and concrete beam object with dimension of length, width and height 60 cm, 15 cm, and 15 cm respectively. Tests were performed at 28-days of concrete. While the addition of bendrat wire fiber is done based on the percentage of volume fraction (Vf) addition to the volume of concrete by 0%; 0,299%; 0,695%; and 0,990%. Each variation was made 9 test specimens consisting of 6 cylinders and 3 beams.The average compressive strength in high quality concrete without bendrat wire has the highest value of 50,0118 MPa. For the average compressive strength value at Vf 0.299%, 0.695%, and 0.990% were 42,2741 MPa, 41,8967 MPa and 39.6320 MParespectively. While for splitting strength and flexural strength in high quality concrete with volume fraction (Vf) 0,990% has the highest value with the splitting strength of an average of 4,6945 MPa and the average flexural strength of 7,9133 MPa Keyword : High quality concrete, bendrat wire fiber